JUSTIFICATION OF THE FINANCIAL-CREDIT INSTRUMENTS CHOICE FOR ENSURING THE RESIDENTIAL REAL ESTATE MARKET FUNCTIONING EFFICIENCY - Dmytro Shteingauz (Consilium LLC, 2021)
The concept "efficiency of the residential real estate market" was considered and the criteria for its analysis were clarified in this study.  The indicators for the residential real estate market functioning effectiveness assessment, income formation components, and investors' expenses for different ways for residential real estate use were determined. A scientific-methodological approach for assessing the effectiveness of the financial-credit instrument in the residential real estate market was suggested, based on determining the real current cash flow value. At the same time, the financial-credit instruments' influence level on the residential real estate market efficiency ensuring was proposed to determine by the taxonomic approach on PATTERN method. This method will allow to compare these instruments in terms of efficiency impact and group them according to investment attractiveness levels